Techno-economic studies of environmentally friendly Brayton cycles in the petrochemical industry - Nkoi, Barinyima (Cranfield University, 2014)
Brayton cycles are open gas turbine cycles extensively used in aviation and industrial applications because of their advantageous volume and weight characteristics. With the bulk of waste exhaust heat and engine emissions associated, there is need to be mindful of environmentally-friendliness of these engine cycles, not compromising good technical performance, and economic viability. This research considers assessment of power plants in helicopters, and aeroderivative industrial gas turbines combined-heat-and-power (ADIGT-CHP) in the petrochemical industry. Thus, it consists of two parts: part A focuses on performance analysis of helicopter gas turbines, while part B entails technoeconomic and environmental risk assessment of ADIGT-CHP in the petrochemical industry. The investigation encompasses comparative assessment of simple cycle (SC) and advanced gas turbine cycle options including the component behaviours and the environmental and economic analysis of the systems. The advanced cycles considered include: recuperated (RC), intercooled (IC), intercooled-recuperated (ICR), and low pressure compressor zero-staged (LPC-ZS), cycles. The helicopter engines are analysed and subsequently converted to small-scale ADIGT engines. Also, modelling combined-heat-and-power (CHP) performances of small-scale (SS), and large-scale (LS) ADIGT engines is implemented. More importantly, a large part of the research is devoted to developing a techno-economic model for assessing, predicting, and comparing viability of simple and advanced cycle ADIGT-CHP in the petrochemical industry in terms of net present value (NPV), internal rate of return (IRR), and simple payback period (SPBP). The techno-economic performances of the ADIGT-CHP cycles are measured against the conventional case of grid power plus on-site boiler. Besides, risk and sensitivity of NPV with respect to uncertain changes in grid electricity cost, gas fuel cost, emission cost, and electricity export tariff, are investigated. Two case studies underlie the development of the techno-economic model. One case study demonstrates the application of the model for large-scale (LS) ADIGT-CHP, and the other for small-scale (SS) ADIGT-CHP, all in the petrochemical industry. By so doing, techno-economic and environmental risk analysis framework (a multi-disciplinary preliminary design assessment tool comprising performance, emissions, economic, and risk modules) is adapted to ADIGT-CHP in the petrochemical industry, which is the aim of this research. The investigation and results led to the conclusions that advanced cycle helicopter and ADIGT engines exhibit higher thermal efficiencies than simple cycle, and that savings exist in operational costs of ADIGT-CHP above the conventional case. Thus, for both SS ADIGT-CHP, and LS ADIGT-CHP cases, all ADIGT-CHP cycles are profitable than the conventional case. For LS ADIGT- CHP category, the IC ADIGT-CHP is the most profitable, whereas for SS ADIGT-CHP category, the RC ADIGT-CHP is the most profitable. The contribution to knowledge of this research is the development of a technoeconomic model for assessing, predicting, and comparing viability of simple and advanced cycle ADIGT-CHP in the petrochemical industry in terms of NPV, SPBP, and IRR over the conventional case of grid power plus on-site boiler. A second contribution is the derivation of simple and advanced cycle small-scale ADIGT and ADIGT-CHP from helicopter engines. Cont/D.
Keywords: Aero-derivative gas turbines; combined-heat-and-power; gas turbine performance; Techno-economic analysis; risk assessment; net present value